1 Korintiërs 9:24-27 – Kerklike leierskap vra ‘n besondere vorm van selfbeheersing - Bredenkamp, D. S. M. (Verbum et ecclesia, 2007)
The purpose of this article is to describe Paul’s self-control in 1 Corinthians 9 as an example to contemporary church leaders. After ascertaining the framework of 1 Corinthians 8:1 to 11:1 as following Christ in loving servitude, Paul’s introducing of his apostleship is described as a combination of an example and a defense. He utilizes the agon motif to make his point regarding his own sacrifices. To him self-control enkrateia) has a finite meaning: to relinquish certain liberties and rights for the sake of his mission in Christ, the identity of the church and the perseverance of his fellow believers. Church leaders can take heed of this necessity for restriction of personal liberty in response to the views of others.